Preparation and Characterization of Biochars for their Application as a Soil Amendment - Das, Shaon Kumar; Ghosh, Goutam Kumar; Avasthe, R. K.; Kundu, Manik Chandra (Indian Journal of Hill Farming, 2018)
Biochar enjoys considerable interest due to its potential to alleviate numerous problems of environmental protection. Various types of biomass can be used as feedstock for biochar production. The kind of matter used as feedstock has an effect on biochar properties. Hence the importance is on proper selection of raw biomass, which will subsequently determine the properties of the biochar. Experiments were conducted to assess the recovery and characterization of biochar derived from six different weed biomass and three different plant biomass at ICAR Research Complex for NEH Region, Sikkim Centre. Charring was carried out in a portable metallic drum (kiln) to make the process simple,quick and low cost. Biochar production efficiency of Lantana camera, Ageratum spp., Neyraridia spp., Artemisia vulgaris,Bidens spp. Chromolaenaodorata, maize stalk, black gram stover and pine needle were 23.2, 13.2, 19.6, 15.1, 14.6, 16.4, 31.7, 27.3 and 18.9%, respectively. The soil reaction indicator pH was 9.21, 9.02, 8.87, 8.53, 8.11, 8.02, 9.38, 9.03 and 8.91, respectively for the above mentioned biochar. Total nitrogen content (g/kg) was highest in black gram stover (12.8) and lowest in Lantana camara biochar (7.2). Alkalinity was highest in maize (135.2) and lowest in Chromolaenaodorata biochar (90.6). Temperature 4500C was best for the preparation of biochar. It was also found that maizebiochar showed good quality properties as compared to other biochar. But all of them can be effectively used as potential source of soil amendment due to their alkalinity in nature.